2016
DOI: 10.1186/s12864-016-3027-1
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional time-course analysis of oral vs. aboral whole-body regeneration in the Sea anemone Nematostella vectensis

Abstract: BackgroundThe ability of regeneration is essential for the homeostasis of all animals as it allows the repair and renewal of tissues and body parts upon normal turnover or injury. The extent of this ability varies greatly in different animals with the sea anemone Nematostella vectensis, a basal cnidarian model animal, displaying remarkable whole-body regeneration competence.ResultsIn order to study this process in Nematostella we performed an RNA-Seq screen wherein we analyzed and compared the transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 105 publications
4
71
1
2
Order By: Relevance
“…Key genes found by Schaffer et al (2016) to be differentially expressed in orally regenerating N. vectensis include multiple components of the Wnt pathway, multiple transcription factors and homeobox genes, consistent with results here for E. pallida and with an earlier study on N. vectensis (DuBuc et al 2014). The homeobox gene Otxc was not found in the present study, consistent with it being found to denote physa (foot) not oral regeneration in N.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Key genes found by Schaffer et al (2016) to be differentially expressed in orally regenerating N. vectensis include multiple components of the Wnt pathway, multiple transcription factors and homeobox genes, consistent with results here for E. pallida and with an earlier study on N. vectensis (DuBuc et al 2014). The homeobox gene Otxc was not found in the present study, consistent with it being found to denote physa (foot) not oral regeneration in N.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that N. vectensis is not the most representative model species for anemone regeneration. Multiple recent studies have explored regeneration in N. vectensis from a transcriptional, morphological and cellular perspective (Amiel et al 2015;DuBuc et al 2014;Schaffer et al 2016) and some similarities and differences can be drawn between this species and E. pallida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A long-standing question in the field of regeneration is whether and to what extent embryonic gene programs that are initially used to build an organism are re-used during regeneration (Morgan 1901). Several transcriptomic studies of regeneration have highlighted the importance of re-deployed developmental pathways in axolotl, anole, zebrafish and sea anemones (Bryant et al 2017) (Habermann et al 2004) (Hutchins et al 2014) (Mathew et al 2009) (Rodius et al 2016) (Gardiner et al 1995;Schaffer et al 2016). Many studies have directly compared embryonic and regenerative gene expression of single or groups of genes identifying i) genes that are specific to embryonic development (Binari et al 2013), ii) genes that are specifically expressed or required during regeneration (Millimaki et al 2010;Katz et al 2015), and iii) embryonic genes that are re-used during regeneration to some extent (Imokawa and Yoshizato 1997) (Carlson et al 2001) (Torok et al 1998) (Özpolat et al 2012) (Wang and Beck 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nematostella has long been used as a model system for embryonic development, the evolution of body patterning, and gene regulatory networks (Hand and Uhlinger 1992;Wikramanayake et al 2003;Hutchins et al 2014; Wang and Beck 2014). More recently, Nematostella has emerged as a powerful whole-body regeneration model as it capable of re-growing missing body parts in less than a week (Burton and Finnerty 2009;Trevino et al 2011;Passamaneck and Martindale 2012;Bossert et al 2013;Dubuc et al 2014;Amiel et al 2015;Schaffer et al 2016) Regeneration in Nematostella follows a dynamic but highly stereotypical morphological and cellular program involving tissue rearrangement and the de novo formation of body structures (Amiel et al 2015).…”
Section: Introductionmentioning
confidence: 99%